Expert opinions regarding neuro-microcirculatory, vestibular and labyrinthine dynamics in benign paroxysmal positional vertigo - Benny, Rajesh (International Journal of Research in Medical Sciences, 2022)
Benign paroxysmal positional vertigo (BPPV) is a common vestibular disorder and a leading cause of peripheral vertigo in adults. The current treatment with repositioning maneuvers still leaves some residual dizziness in a significant proportion of patients with BPPV. The role of neuro-microcirculatory, vestibular, and labyrinthine dynamics needs to be evaluated. Eighty leading neurologists and otolaryngologists from across India participated in advisory board meetings to debate on altered neuro-microcirculatory, vestibular, and labyrinthine dynamics in BPPV. Betahistine when used in conjunction with Epley maneuver was considered to be a safe treatment. Betahistine can be used as monotherapy in patients with BPPV who are deemed unfit to undergo canalolith repositioning maneuvers. Betahistine provides short-term relief from acute symptoms associated with BPPV by improving microcirculation in the labyrinth and improves vestibular compensation, thereby providing long-term benefit. Betahistine also improves outcomes in combination with canalolith repositioning maneuvers. Experts unanimously agreed upon the role of betahistine in providing better vestibular health and in-turn, recovery from vertigo.